Pengaruh Penggunaan Media Audio Visual Terhadap Hasil Belajar Dribble Bola Basket Kelas XI SMA Negeri 15 Semarang Tahun Ajaran 2020 - Novan Pinar Arwanda; Pandu Kresnapati; Fajar Ariwidyatmoko (YLPK Mahardhika, 2021)
The background of the problem in this study was the lack of students' ability to perform basic basketball dribbling techniques because the students did not master the basic techniques of playing basketball. The purpose of this study was to determine how influential the audio-visual media on Dribble learning is to improve basketball Dribble learning outcomes. This study uses a Quasi Experiment Design. The sampling technique was carried out by purposive sampling. A total of 67 samples with 2 experimental classes, namely class XI MIPA 1 with a total of 30 students and class X1 MIPA 7 with a total of 35 students. Data analysis techniques used the normality test and t-test which were processed with the help of SPSS 16 software. The results of this study were obtained by analyzing the Dribble learning outcomes with the Audio visual learning model These results can be concluded that the significance value of both is more than 0.05. This means that there is no significant difference between the effect of audio visual media and Dribble learning on basic basketball technical skills